2016
DOI: 10.1074/mcp.m115.057364
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Dynamics and Stoichiometry of the Apoptosis Signal-regulating Kinase (ASK) Signalosome in Response to Electrophile Stress

Abstract: Apoptosis signal-regulating kinase 1 (ASK1) is a key sensor kinase in the mitogen-activated protein kinase pathway that transduces cellular responses to oxidants and electrophiles. ASK1 is regulated by a large, dynamic multiprotein signalosome complex, potentially including over 90 reported ASK1-interacting proteins. We employed both shotgun and targeted mass spectrometry assays to catalogue the ASK1 protein-protein interactions in HEK-293 cells treated with the prototypical lipid electrophile 4-hydroxy-2-none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 69 publications
2
32
1
Order By: Relevance
“…This behaviour suggests that the SAM domains of each protein contribute markedly to the heterotypic ASK1-ASK2 complexes previously reported (4)(5)(6)(7)(8)28).…”
Section: Figure 3: Heterotypic Interactions Between Ask Sam Domains (supporting
confidence: 69%
See 2 more Smart Citations
“…This behaviour suggests that the SAM domains of each protein contribute markedly to the heterotypic ASK1-ASK2 complexes previously reported (4)(5)(6)(7)(8)28).…”
Section: Figure 3: Heterotypic Interactions Between Ask Sam Domains (supporting
confidence: 69%
“…When transfected together, wild-type ASK1 and ASK2 show significantly lower basal levels of kinase activity, which is nonetheless activated by HNE. Based on the complete lack of signal in cells transfected with ASK2 alone (WT or C1268E; Figure 4A/B central lanes), the phospho-ASK signal is specific to ASK1, rather than cross-reactivity of the ASK1- Elegant endogenous mass spectrometry studies have previously shown that ASK1 associates with near-stoichiometric amounts of ASK2 (28). We employed an orthogonal approach-bimolecular complementation affinity purification (BiCAP (29,30))-to determine if stoichiometric association of ASK1-ASK2 occurs as part of larger hetero-oligomeric complex.…”
Section: Sam-mediated Oligomers Regulate Activity and Stoichiometry Imentioning
confidence: 98%
See 1 more Smart Citation
“…SAINT assigns each protein a SAINT Probability Score ("P-Score"), on a scale of 0 to 1, with 1 being the top score. Based upon review of the literature, we chose 0.65 as a SAINT cut-off score for enrichment (68)(69)(70)(71)(72)(73). With the approach used here, all proteins have two P-Scores, one each for basal or insulin enrichment over the respective negative controls.…”
Section: Resultsmentioning
confidence: 99%
“…1A). The active signaling form of ASK1 in cells is thought to be an oligomer often referred to as the "ASK signalosome," which also contains ASK2 and ASK3 (20)(21)(22). To the N terminus of the kinase domain lie several regions with regulatory roles but poorly understood structures.…”
mentioning
confidence: 99%